2021
DOI: 10.5114/wo.2021.111310
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on the management of head and neck cancer patients at a tertiary care institution in Poland

Abstract: Aim of the study: To assess the impact of the COVID-19 pandemic on the diagnosis and treatment of patients at a tertiary hospital in Poland. Material and methods: This was a retrospective review of head and neck cancer patients who presented to the multidisciplinary tumour board (MTB) during the 12-month period from March 2020 to February 2021 and compared to patients who presented to the MTB during the prior, pre-pandemic 12-month period from February 2019 to March 2020: Patient demographic and clinical varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Moreover, cancer centres remained open throughout the pandemic, whereas other hospitals were mainly responsible for treating patients with COVID-19. This phenomenon was described in a study by Szewczyk et al [17], which included HNC patients treated at the Cancer Centre in Poznan. The authors compared the characteristics of patients diagnosed with HNC during the 12-month pre-pandemic period prior to the implementation of pandemic-related restrictions in Poland in March 2020 with those of patients diagnosed and treated during the pandemic (March 2020-February 2021).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, cancer centres remained open throughout the pandemic, whereas other hospitals were mainly responsible for treating patients with COVID-19. This phenomenon was described in a study by Szewczyk et al [17], which included HNC patients treated at the Cancer Centre in Poznan. The authors compared the characteristics of patients diagnosed with HNC during the 12-month pre-pandemic period prior to the implementation of pandemic-related restrictions in Poland in March 2020 with those of patients diagnosed and treated during the pandemic (March 2020-February 2021).…”
Section: Discussionmentioning
confidence: 79%
“…The literature in this area provides various results. In a study by Szewczyk et al [17], the mean time from the first visit to the multidisciplinary tumour board meeting differed slightly (but not significantly) between the pre-COVID-19 pandemic period and the period of the COVID-19 pandemic. Zubair [23] confirmed that there was no delay in the initiation of first treatment after the decision to treat.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Long-term oncologic outcomes will also be important to evaluate in this population with comparison to patients from previous years. Future studies should be dedicated to evaluating both COVID-related and oncologic long-term outcomes in these vulnerable patients, especially in the context of profound changes in cancer care delivery during the pandemic [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Odnotowano m.in. znaczny spadek średniej liczby pacjentów rozpoczynających radioterapię [40], wydłużenie czasu od pierwszej wizyty do rozpoczęcia leczenia [41] oraz mniej wstępnych rozpoznań i rozszerzonych badań diagnostycznych i konsyliów onkologicznych [42], a także znaczne zmniejszenie liczby wykonywanych zabiegów operacyjnych [43,47] u pacjentów z chorobą nowotworową, chociaż w niektórych badaniach wskazywano na dostosowanie się systemu do zaistniałej sytuacji i stosunkowo szybki powrót do realizacji świadczeń na poziomie liczebnym sprzed pandemii [44,46]. Autorzy pracy zaznaczają konieczność prowadzenia dalszych obserwacji, aby określić długoterminowy wpływ pandemii na trendy i leczenie onkologiczne, ponieważ niekorzystne skutki mogą być opóźnione [45,46].…”
Section: Badania Dotyczące Leczenia Chorób Układu Krążeniaunclassified